GASTRIC SCHWANNOMA - Bukhsh, Sumaira; Muhammad, Iqbal; Ahmed, Saeed; Hashmi, Shoaib Naiyer; Kamran, Muhammad (Pakistan Armed Forces Medical Journal, 2017)
Schwannomas are generally benign, slow growing tumors, which can originate from any nerve that has a schwann cell sheath. Digestive tract schwannomas are very rare. We will disuss the case of a 55 year-old man who was operated for gastrointestinal stromal tumour (GIST) but histopathology revealed gastric schwannoma. This case emphasized on the fact that for every exophytic submucosal gastric mass, gastric schwannomas must be considered as one of the differential diagnosis. Study at our institute of Armed Forces Institute of Rawalpindi diagnosed 46 gastric GIST for each gastric schwannoma.